Experiences of Self-Intentional Abortion among a Group of Marginalized Middle-Eastern Women: A Feminist Critical Discourse Analysis - Shirali, Sahar (Hawwa, 2025)
Abortion is a sensitive and complicated issue worldwide, especially, in sociocultural contexts where it is legally restricted or socially stigmatized. This study is concerned with examining Qashqai Turkic women’s experiences of self-intentional abortion in Iran where termination of a pregnancy is banned and criminalized by law. To this aim, six women aged 25 to 44, living in Iran, all of whom were born and raised in Qashqai Turkic families, with at least one self-intentional abortion from 2014 to 2023, were interviewed in this study. The narratives were analyzed qualitatively based on Feminist Critical Discourse Analysis (Lazar, 2005, 2007 and 2014) which revealed that all these women experienced negative physical repercussions, especially, mental repercussions after their abortion. Most of these women regarded these repercussions as the aftermath of not having access to safe abortions and post-abortion care as well as the oppressive view concerning women’s rights which is quite evident in small communities.